2018
DOI: 10.1186/s42358-018-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Hand strength in patients with RA correlates strongly with function but not with activity of disease

Abstract: Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic inflammation of the joints, especially of the hands. The evaluation of handgrip strength (HS) and pinch strength can be useful to detect reduction in hand function in RA patients. The aim of the study was to compare HS and pinch strength between RA patients (RA Group-RAG) and a non-RA control group (CG) and to relate HS and pinch strength to functional capacity, duration and disease activity in the RAG. Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
3
17
1
1
Order By: Relevance
“…Current study results were matching with Bircan et al's [21] and Verma and his colleagues' [4] studies where GAT scores were seen affected in 95 % of the studied RA patients. These findings were in agreement with the findings of Silva et al [22] who found that the handgrip strength was weak among the patients with RA compared with the controls. This is attributed to the joint damage, pain, and muscle weakness due to disuse and disease progression [23].…”
Section: Discussionsupporting
confidence: 93%
“…Current study results were matching with Bircan et al's [21] and Verma and his colleagues' [4] studies where GAT scores were seen affected in 95 % of the studied RA patients. These findings were in agreement with the findings of Silva et al [22] who found that the handgrip strength was weak among the patients with RA compared with the controls. This is attributed to the joint damage, pain, and muscle weakness due to disuse and disease progression [23].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, reduced handgrip strength was correlated with increased risk of chronic diseases and mortality, and reduced long-term functional capacity (35,37,38). In patients with systemic autoimmune diseases, impaired strength in this test is also related to reduced functional capacity or activities of daily living, thus corroborating our study's findings (14,39).…”
Section: Original Papersupporting
confidence: 86%
“…strength resulting from long-term vascular claudication (13,14 ORIGINAL PAPER and rested for 5 minutes before starting the measurement. The arm to be measured remained supported and extended at the height of the sternum, and the cuff was positioned around the arm and correctly adjusted.…”
Section: Original Papermentioning
confidence: 99%
“…Our study obtained an average of 14.5 in CHFS, indicating a loss in functionality; it is important to emphasize that these patients have difficulties in specific tasks, like buttoning a shirt and peeling fruit, that prevents daily domestic tasks. It is also emphasized that the impairment of hand function in SSc can be similar or even worse than that described in other diseases that present with joint involvement of the hands, such as rheumatoid arthritis 20 or osteoarthritis.…”
Section: Discussionmentioning
confidence: 83%